Hubungan Antara Lama Menderita Diabetes Dengan Nilai Ankle Brachial Index - Taufik Dwi Cahyono; Okti Sri Purwanti (Jurnal Berita Ilmu Keperawatan, 2019)
Duration of suffering diabetes melitus type 2 causes glucose increase in blood results in blood vessels damage, creates a risk of complications which will usually appear in 5-10 years. Further examination is needed is to measure Ankle brachial index (ABI), which is the ratio of blood pressure in the ankle and arm. The purpose of this research was to investigate the relationship between duration of diabetes melitus and an ankle brachial index in patients with type 2 diabetes melitus in Hospital Dr. Moewardi Surakarta. This research is a descriptive correlative with cross sectional approach. The sample used in this study 30 patients with type 2 diabetes melitus who were hospitalized in Dr. Moewardi Surakarta Hospital. Sampling technique used is consecutive sampling. The instrument used to record data are questionnaires, sphygmomanometer and stethoscope. Analysis of the data used is the chi square test. Bivariat results found that respondents who had normal ABI values with the duration of diabetes 0.05), which means that Ho is accepted. The conclusions of this study indicate that there is no relationship between duration of diabetes melitus with an ankle brachial index in patients with diabetes melitus type 2 whichmeans that the duration of diabetes melitus does noteffect the value abnormality ABI.